Cloud computing role to address Mobile Learning barriers: An exploratory study of HEIs in Malaysia - Al-Arabiat, D. (Institute of Electrical and Electronics Engineers Inc., 2016)
Mobile Learning (M-Learning) is considered as an effective way to enhance the learning process between Higher Education Institutions (HEIs). Despite the increasing usage of m-learning, employing its full benefits is difficult due to mobile device problems such as resource scarcity and frequent disconnections. This study aims to examine the barriers to adopt m-learning by HEIs in Malaysia and explore the role of cloud computing in addressing these barriers and improve m-learning. To do so, an online questionnaire was developed. The questionnaire was distributed by email to 150 respondents (students) from three different universities in Malaysia. The result analysis brought out that mobile storage size, limitation of mobile memory and mobile battery life are the main barriers of using mobile in the learning process. And, most importantly, the majority of respondents strongly agree with the main role of cloud computing as a support for mobile learning. Â© 2016 IEEE.